The Effect of Economic Growth, Inflation Rate, and Interest Rates of Bank Indonesia on the Composite Stock Price Index on the Indonesia Stock Exchange for the 2015-2019 Period: Pengaruh Pertumbuhan Ekonomi, Laju Inflasi, Dan Tingkat Suku Bunga Bank Indonesia Terhadap Indeks Harga Saham Gabungan Di Bursa Efek Indonesia Periode 2015-2019 - Ahmad Firdausi Akmal Al Haytami; Heri Widodo (Academia Open, 2021)
Generally, investors use the Composite Stock Price Index (IHSG) as a parameter of stock performance listed on the Indonesian stock exchange. One of the factors that can affect the JCI is macroeconomic factors such as economic growth, inflation, and interest rates. This study aims to determine the effect of economic growth, inflation rate, and interest rates of Bank Indonesia on the JCI. The population and samples in this study are quarterly economic growth, inflation, Bank Indonesia interest rates, the monthly Composite Stock Price Index (JCI) from 2015-2019. Testing the hypothesis of this study using the validity and reliability test with the SmartPLS version 3. The results showed that the variables of economic growth and inflation had no significant effect on the Composite Stock Price Index (JCI). Meanwhile, the interest rate variable of Bank Indonesia has a significant effect on the JCI.